Z antroponimii Łatgalii (imiona Polaków dyneburskich z lat 1945–1991) - Mordań, Michał (Slavia Orientalis, 2024)
The article shows the hitherto little researched subject of the names of Poles – residents of Dyneburg (Daugavpils) between 1945 and 1991. The purpose of the study is to present a repertoire of the anthroponyms and linguistic characteristics of their forms. The material was collected from entries in registration books (Lat. mājas grāmatas) containing the personal data of the town’s residents. The analysis of the collected material allows us to conclude that regardless of the linguistic genesis, names with religious roots clearly predominated with Dyneburg Polish circles. In terms of the forms used, Russian equivalents are the most numerous, while the presence of Polish variants, emphasizing the nationality of the name bearers, is significant.